2011
DOI: 10.2113/gsjfr.41.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Benthic Foraminiferal Morphogroups on the Argentine Continental Shelf

Abstract: The aim of this study is to evaluate the relative influence of abiotic factors on the association and spatial distribution of recent benthic foraminiferal morphogroups in the Argentine continental shelf at ,40uS environments as a first step towards establishing their paleoecological significance. Foraminifera are classified into five morphogroups: tapered, elongateflattened, milioline, planoconvex, and rounded-planispiral. Compositional data analysis techniques were used to define morphogroup assemblages, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…This species of Buccella is widely distributed in the Bahía Blanca estuary (Cusminsky et al, 2006(Cusminsky et al, , 2009Calvo-Marcilese et al, 2011). It has also been recorded in Holocene material from Bahía Blanca (see sections N1, PS2B2, CdM, C3B in the Figure 1 of this paper, and Gómez et al, 2005;Cusminsky et al, 2009;Calvo-Marcilese et al, 2011) and from late Holocene deposits along north-and south-eastern Buenos Aires province (Boltovskoy, 1970(Boltovskoy, , 1976Laprida, 1998;Laprida et al, 2007;Ferrero, 2006;Alperin et al, 2011). In present-day Bahía Blanca estuary material, Buccella is widely distributed in subtidal and inner shelf environments but has rarely been recovered from intertidal habitats (Cusminsky et al, 2006;Calvo-Marcilese & Pratolongo, 2009).…”
Section: Biogeographysupporting
confidence: 57%
“…This species of Buccella is widely distributed in the Bahía Blanca estuary (Cusminsky et al, 2006(Cusminsky et al, , 2009Calvo-Marcilese et al, 2011). It has also been recorded in Holocene material from Bahía Blanca (see sections N1, PS2B2, CdM, C3B in the Figure 1 of this paper, and Gómez et al, 2005;Cusminsky et al, 2009;Calvo-Marcilese et al, 2011) and from late Holocene deposits along north-and south-eastern Buenos Aires province (Boltovskoy, 1970(Boltovskoy, , 1976Laprida, 1998;Laprida et al, 2007;Ferrero, 2006;Alperin et al, 2011). In present-day Bahía Blanca estuary material, Buccella is widely distributed in subtidal and inner shelf environments but has rarely been recovered from intertidal habitats (Cusminsky et al, 2006;Calvo-Marcilese & Pratolongo, 2009).…”
Section: Biogeographysupporting
confidence: 57%
“…According to Usera and Blázquez-Morilla (1997), the resistance to erosion of shells in the Order Miliolida favors their relative abundance. Alperin et al (2011) and Bernasconi, 2020) reported that epifaunals as miliolids are associated to sandy sediments and high-energy environments. Genera that get attached to the substrate, such as Quinqueloculina spp.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in the infaunal forms is probably due to the presences of muddy sediment that prevails in this upper part of the sequence. In addition, Bernasconi and Cusminsky (2009), Bernhard et al (1997), Hayward et al (2002), Sen Gupta and Machain-Castillo (1993), Smart (2002), and Alperin et al (2011) concluded that some Bolivina, Bulimina and other biserial species are adapted to living in zones with minimum oxygen levels. The increase in these infaunal species together with the data obtained from the indexes would reflect eutrophic conditions with lower oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…The assessed morphological diversity is consequently above the species level. Simplification of information is a risk of the morphological group approach (Read et al, 2014), but it provides access to a partition of variability that is potentially more informative ecologically than taxonomically when the studied biological object is sensitive to environmental change (Alperin, Cusminsky, & Bernasconi, 2011;Read et al, 2014;Khare et al, 2017), which is the case for shrew mandibles (Badyaev & Foresman, 2000;Young et al, 2010). The morphological groups reveal variations in the number of morphotypes independent of the number of species.…”
Section: Morphological Groupsmentioning
confidence: 99%